WAYANG KULIT AS A WORLD ATTRACTION FOR YOGYAKARTA TOURISM: A STUDY OF WAYANG KULIT PERFORMANCES IN KRATON YOGYAKARTA - Lutfi Maulana Hakim; Weka Kusumastiti (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Wayang Kulit (leather shadow-puppet play) is one of Indonesia's original cultures that was included in the UNESCO Intangible Cultural Heritage. The Ngayogyakarta Hadiningrat Palace, the center of cultural arts in Yogyakarta, regularly shows wayang kulit performances as cultural arts performances. Wayang kulit performances at the Yogyakarta Palace were held every Thursday from 10.00 - 13.00 WIB in Bangsal Srimanganti of Yogyakarta Palace. By looking at the phenomenon of wayang kulit performances at the Srimanganti Palace, the researcher wants to see how far the role of wayang kulit as a global cultural heritage has become a tourist attraction in Yogyakarta. The global role of wayang kulit as a tourism attraction will be studied using the concept of 4A Tourism (Attractions, Amenities, Accessibility, Ancillary) combined with the theory of the Global Village by Marshall McLuhan. The findings show that the management of cultural tourism in the Yogyakarta Palace has successfully implemented the 4A concept in tourism. The application of this concept has had many effects on the sustainability of tourism in the Yogyakarta palace, especially wayang kulit performances.Keywords: Wayang Kulit, Puppet Show, Yogyakarta Palace, Cultural Heritage